2014
DOI: 10.1016/j.apergo.2013.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Postural stability when walking: Effect of the frequency and magnitude of lateral oscillatory motion

Abstract: While walking on an instrumented treadmill, 20 subjects were perturbed by lateral sinusoidal oscillations representative of those encountered in transport: frequencies in the range 0.5 to 2 Hz and accelerations in the range 0.1 to 2.0 ms -2 r.m.s., corresponding to velocities in the range 0.032 to 0.16 ms -1 r.m.s. Postural stability was assessed from the self-reported probability of losing balance (i.e., perceived risk of falling) and the movements of the centre of pressure beneath the feet. With the same acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 21 publications
2
15
1
Order By: Relevance
“…This study created this scenario for testing, it was considered the misuse scenario. The platform motions caused by the fall-arrest conditions evaluated in this study similar to or worse than those found in the aforementioned research (Wertheim, 1998, Sari and Griffin, 2014, and Duncan et al, 2014). …”
Section: 0 Discussion and Conclusionsupporting
confidence: 81%
See 1 more Smart Citation
“…This study created this scenario for testing, it was considered the misuse scenario. The platform motions caused by the fall-arrest conditions evaluated in this study similar to or worse than those found in the aforementioned research (Wertheim, 1998, Sari and Griffin, 2014, and Duncan et al, 2014). …”
Section: 0 Discussion and Conclusionsupporting
confidence: 81%
“…Lateral sinusoidal oscillations from 0.5–2 hertz and accelerations from 0.1–2.0 m/s 2 (0.33–6.56 ft/s 2 ) were shown to cause postural instability and the perceived risk of falling (Sari and Griffin, 2014). Repeated exposures to platform motions can also affect the human response—more exposure to the movement the better the adaptation to the movement (Duncan et al, 2014).…”
Section: 0 Discussion and Conclusionmentioning
confidence: 99%
“…Control of balance, or postural stability, is essential in all static and dynamic activities [5]. Maintaining balance is more challenging when there are external disturbances from motion of the floor, such as when standing or walking in a moving train, bus, aircraft or ship [6]. Healthy subjects who experience a sudden postural disturbance while standing recover postural stability using appropriate movement strategies involving agonist and antagonist muscle groups according to the environmental context [7].…”
Section: Introductionmentioning
confidence: 99%
“…14 With sinusoidal oscillation of a platform in the mediolateral axis of walking subjects, their postural stability was similar when motions had the same velocity, irrespective of the frequency of oscillation in the range 0.5 to 2 Hz. 15 Apart from quantifying motions to predict walking instability, discomfort or difficulty, postural stability research has also sought metrics to identify walking balance. Understanding how people maintain stability when walking, particularly when exposed to perturbations, is key to preventing falls, but there is no universally accepted measure of stability.…”
Section: Introductionmentioning
confidence: 99%